Studying the Usability of an Intervention to Promote Teachers' Use of Robotics in STEM Education. (January 2019) - Kim, ChanMin; Yuan, Jiangmei; Kim, Dongho; Doshi, Prashant; Thai, Chi N.; Hill, Roger B.; Melias, Ernst
We developed RoboSTEM, a portal for open educational resources for the use of robotics in teaching and learning, to help teachers learn how to design and implement lessons using robotics. In this article, the design and functionality of RoboSTEM and the theoretical foundations behind its design are described. Two usability testing studies are also presented. Participants were 13 pre- and in-service teachers. Results from both quantitative and qualitative data analyses show that (a) usability survey ratings were positive overall and improved after revisions from the first usability study to the second; (b) data from participants' screen activities and interviews were aligned with the survey results; (c) high levels of behavioral, cognitive, and emotional engagement in RoboSTEM were observed; and (d) the positive impact of RoboSTEM on example-based learning was acknowledged among teachers. Applications of RoboSTEM as well as future research and development directions are discussed.